2018
DOI: 10.1007/s00586-017-5459-y
|View full text |Cite
|
Sign up to set email alerts
|

Normal variation in sagittal spinal alignment parameters in adult patients: an EOS study using serial imaging

Abstract: Radiographic sagittal parameters vary between serial images and reflect dynamism in spinal balancing. SVA and PT are predisposed to the widest variation. SVA has the largest variation between individuals of low pelvic tilt. Therefore, interpretation of these parameters should be patient specific and relies on trends rather than a one-time assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…However, no previous studies have been conducted on patients who require surgical treatment, and clinically, EOS is often part of a preoperative analysis, which necessitates research on patients who underwent surgery. In our study, most sagittal alignment parameters on serial EOS imaging did not show statistically significant interval changes even in patients requiring surgical treatment, which can be interpreted in the same context as the results of a previous study [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, no previous studies have been conducted on patients who require surgical treatment, and clinically, EOS is often part of a preoperative analysis, which necessitates research on patients who underwent surgery. In our study, most sagittal alignment parameters on serial EOS imaging did not show statistically significant interval changes even in patients requiring surgical treatment, which can be interpreted in the same context as the results of a previous study [17].…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Kim et al, the EOS system showed excellent intra-rater (intraclass correlation coefficients (ICCs) ranging from 0.898 to 0.982) and interrater reliability (ICC ranging from 0.794 to 0.837) in the assessment of the sagittal alignment of the spine and pelvis [15]. A recent study measuring all sagittal radiographic parameters in patients with first-episode mild low back pain to describe normal variation showed small mean variations (<1 • ), except for in pelvic tilt (PT) (1.2 • ), C2-T1 alignment (1.2 • ), and SVA (2.9 cm) [17]. This result guarantees the reliability of EOS imaging in normal adult patients and raises the possibility of inconsistency in some parameters due to the dynamic nature of body balance [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant body of work has been completed to define normal alignment of the spine in the adult population, such effort remains lacking in children (Asai et al, 2017;Boseker et al, 2000;During et al, 1985;Hasegawa et al, 2016;Hey et al, 2018;Jackson et al, 2000;Le Huec et al, 2011). Only a few studies have attempted to analyze and define normal alignment values in children, yet these have been variable in methodology and frequently have considered global spinal parameters rather than focus on segmental values (Bailey et al, 2019;Cil et al, 2005;Dolphens et al, 2013;Ghandhari et al, 2013;Lee et al, 2012;Lee et al, 2014;Mac-Thiong et al, 2004;Mac-Thiong et al, 2007;Mangione et al, 1997;Marty et al, 2002;Masharawi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding normal alignment of the spine is desirable as it allows clinicians to define surgical goals and explore possible pathomechanics in the abnormal (Duval-Beaupere et al, 1992;Legaye et al, 1998). To date much of the available data are based on adult cohorts with various methodology adopted to explore the influence of factors such as age, sex, and ethnicity on spinal and sacropelvic parameters (Asai et al, 2017;Hasegawa et al, 2016;Hey et al, 2018). The relationship of the pelvic incidence (PI) and lumbar lordosis is well described and now underpins many treatment decisions (Anwar et al, 2015;Pesenti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%